Building Brand Image through Social Media Marketing and Service Quality to Improve Marketing Perfomance - Wiedayanti, Destine Fajar; Karnowahadi; Bagus Yunianto Wibowo; Subandi (Politeknik Negeri Semarang, 2025)
Marketing by utilizing internet media or electronic marketing (e-marketing) has increased significantly. This is supported by technological developments that are growing rapidly because of the internet which helps make it easier to find information, communicate without limits, and distance. This study aims to determine how the Effect of Social Media Marketing and Service Quality on Brand Image in Food Processed MSMEs in Semarang City. While the sampling technique used in this research is the Purposive Sampling Method. The number of research samples was 100 samples from the total population of respondents. This research technique uses two approaches: 1). Confirmatory factor analysis, on Structural Equation Modeling (SEM); and 2). Regression Weight on Structural Equation Modeling (SEM). The model output in this study can make a positive contribution to Food Processed MSMEs in Semarang City in an effort to realize the continuity and sustainability of their business in marketing performance, both in the form of managerial implication suggestions and formulation of scientific articles and measurement instruments. Managerial advice is aimed at food processing MSMEs in formulating strategies to maintain their business so that consumers come back to buy food processing MSME products. Pemasaran dengan media internet atau electorinc marketing (e-marketing) mengalami peningkatan signifikan. Hal ini didukung oleh perkembangan teknologi yang semakin berkembang dengan pesat karena adanya internet yang membantu mempermudah mencari informasi, berkomunikasi tanpa batas, dan jarak. Penelitian ini bertujuan untuk mengetahui bagaimana Pengaruh Social Media Marketing dan Service Quality Terhadap Brand Image pada UMKM Olahan Pangan di Kota Semarang. Sedangkan Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah Metode Purposive Sampling. Untuk jumlah sampel penelitian adalah 100 sampel dari total populasi responden. Teknik penelitian ini mengunakan dua pendekatan: 1). Confirmatory factor analysis, pada Structural Equation Modeling (SEM); dan 2). Regression Weight pada Structural Equation Modeling (SEM). Luaran model pada penelitian ini dapat memberikan konstribusi positif bagi UMKM Olahan Pangan di Kota Semarang dalam upaya untuk dapat mewujudkan continuity dan Sustainibility usaha mereka dalam kinerja pemasaran, baik dalam bentuk saran implikasi manajerial dan rumusan artikel ilmiah serta instrumen pengukuran. Saran manajerial ditujukan bagi UMKM Olahan Pangan dalam merumuskan strategi guna mempertahankan bisnisnya agar konsumen kembali lagi untuk membeli produk UMKM Olahan Pangan